Clinical phenotype and current diagnostic criteria for primary ciliary dyskinesia. (1st November 2016) - Dehlink, Eleonora; Hogg, Claire; Carr, Siobhan B.; Bush, Andrew
ABSTRACT: Introduction : Primary ciliary dyskinesia (PCD) is a rare, mostly autosomal-recessive disorder of motile cilia, characterized by chronic lung disease, rhinosinusitis, hearing impairment, and subfertility. PCD is still often missed or diagnosed late since symptoms overlap with common respiratory complaints, but should be considered if one or more of the cardinal clues are present. Areas covered : We provide an overview on clinical presentations of PCD and clues for when to consider PCD, these include unexplained neonatal respiratory distress, persistent rhinitis from the first days of life, situs anomalies, or otorrhoea following tympanostomy tube insertion. Diagnosis is on the basis of clinical suspicion, and an algorithm of nasal nitric oxide, ciliary beat pattern and frequency, transmission electron microscopy, immunofluorescence of ciliary proteins and genetic studies. However, there is no one gold-standard test as yet. We reviewed the current literature based on PubMed and Ovid databases literature search. Expert commentary : There is a need for increased awareness about PCD beyond specialist respiratory clinicians and a need for standardization of PCD diagnostics internationally. Early diagnosis means that inappropriate treatment based on misdiagnosed conditions can be avoided, and the onset of bronchiectasis may be delayed.